2019
DOI: 10.3389/feart.2019.00306
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Imaging of Cadmium Sorption and Transport in Porous Rocks

Abstract: Understanding fluid flow in rocks is crucial to quantify many natural processes such as ground water flow and naturally triggered seismicity, as well as engineering questions such as displacement of contaminants, the eligibility of subsurface waste storage, geothermal energy usage, oil and gas recovery and artificially induced seismicity. Two key parameters that control the variability of fluid flow and the movement of dissolved chemical species are (i) the local hydraulic conductivity, and (ii) the local sorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…The Institut Laue‐Langevin in Grenoble, France is a neutron source where high‐speed neutron tomographies with a rapid acquisition time of around 1 minute have been obtained to study water invasion into air‐filled samples of rock (Tudisco et al., 2019). The neutron source SINQ at the Paul Scherrer Institute in Switzerland is another facility where we show in the present study the capability of in situ analysis of the local changes in fluid flow properties of rocks, expanding the possibilities for studying fluid dynamics in rock samples (Cordonnier et al., 2019). In the present study, we quantify the spatial fluctuations of fluid velocity before and after calcium carbonate precipitation in porous sandstone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Institut Laue‐Langevin in Grenoble, France is a neutron source where high‐speed neutron tomographies with a rapid acquisition time of around 1 minute have been obtained to study water invasion into air‐filled samples of rock (Tudisco et al., 2019). The neutron source SINQ at the Paul Scherrer Institute in Switzerland is another facility where we show in the present study the capability of in situ analysis of the local changes in fluid flow properties of rocks, expanding the possibilities for studying fluid dynamics in rock samples (Cordonnier et al., 2019). In the present study, we quantify the spatial fluctuations of fluid velocity before and after calcium carbonate precipitation in porous sandstone.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment BS0 is a test to demonstrate the use of three‐dimensional time‐resolved neutron imaging in investigating fluid mixing phenomena within porous rock. We used two miscible fluids, a solution of deuterium oxide heavy water (D 2 O) and a solution of heavy water with dissolved cadmium (CdCl 2 ), an element that provides good contrast for neutron imaging and that was used in a previous study (Cordonnier et al., 2019). After fully flushing the sample with heavy water, we injected heavy water from one inlet at the top of the core sample and 1 M of CdCl 2 (aq) (dissolved in heavy water) from the other inlet at the top.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment BS0 is a test to demonstrate the feasibility of three-dimensional time-lapse neutron imaging to study fluid mixing in porous rock. We used two miscible fluids, a solution of deuterium oxide heavy water (D 2 O) and a solution of heavy water with dissolved cadmium (CdCl 2 ), an element that provides good contrast for neutron imaging and that was used in a previous study (Cordonnier et al, 2019). After fully flushing the sample with heavy water, we injected heavy water from one inlet at the top of the core sample and 1 M of CdCl 2 (aq) (dissolved in heavy water) from the other inlet at the top.…”
Section: Fluid Mixing Test (Experiments Bs0)mentioning
confidence: 99%
“…They found that after 15 PV water injection, the CO 2 saturation was decreased from 30% to 10%. Moreover, 2D and 3D neutron imaging were used by Cordonnier et al [ 321 ] to study cadmium (a common contaminant in soil and groundwater) sorption and transport in porous media. They performed a series of flow-through experiments on different sandstone and limestone core samples and imaged in-situ flow properties.…”
Section: Applications Of Micromodels and Imaging Techniquesmentioning
confidence: 99%